Enhancing Power Grid Reliability with AGC and PSO: Insights from the Timimoun Photovoltaic Park - Tadjeddine, Ali Abderrazak; Arbaoui, Iliace; Bendjillali, Ridha Ilyas; Chaker, Abdelkader (EAI Endorsed Transactions on Energy Web, 2024)
This article investigates the impact of integrating Variable Renewable Energy (VRE), specifically solar energy from the Timimoun Photovoltaic Park, on the PIAT electrical grid stability in southern Algeria. The study focuses on how fluctuations in power demand and changes in weather conditions can affect grid frequency control, potentially leading to transient stability issues. To address these challenges, the research proposes the implementation of an Automatic Generation Control (AGC) system combined with the Particle Swarm Optimization (PSO) algorithm to optimize solar energy distribution. This approach effectively regulates real-time frequency deviations resulting from VRE integration, ensuring balanced supply and demand, and controllable power factor injection. The findings demonstrate that the integration of AGC and PSO stabilizes the frequency at the Timimoun Photovoltaic Park and reduces total active losses in the PIAT network by 13.88%. Additionally, strategic power factor control at the injection buses ensures optimal power quality and maximizes the utilization of the photovoltaic park, leading to a 4.84% reduction in the PIAT grid’s reliance on gas turbines. This approach contributes to lowering operational costs, reducing carbon emissions, and supporting a transition to greener energy.